The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1744806920969476
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cannabinoid type 1 receptor in fasting-induced analgesia

Abstract: The endocannabinoid system (ECS) is known to modulate not only food intake but also pain, especially via the cannabinoid type 1 receptor (CB1R) expressed throughout the central nervous system and the peripheral tissues. Our previous study demonstrated that fasting produces an analgesic effect in adult male mice, which is reversed by intraperitoneal (i.p.) administration of CB1R antagonist (SR 141716). In the present study, we further examined the effect of CB1R expressed in the peripheral tissues. In the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…While the effect of SDV has been well studied with focus on visceral disease and is critically associated with visceral pain [6,9,12], recent studies have demonstrated that SDV can relieve somatic pain as well [8,13]. We also confirmed SDV-induced analgesia in formalin-induced acute inflammatory pain condition Effect of Subdiaphragmatic Vagotomy on Acute Inflammatory Pain [14]. Given SDV attenuates pain originated from extraterritorial area which is not innervated by vagus nerve, supraspinal mechanisms are highly likely to contribute to SDV-induced analgesia in somatic pain conditions.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…While the effect of SDV has been well studied with focus on visceral disease and is critically associated with visceral pain [6,9,12], recent studies have demonstrated that SDV can relieve somatic pain as well [8,13]. We also confirmed SDV-induced analgesia in formalin-induced acute inflammatory pain condition Effect of Subdiaphragmatic Vagotomy on Acute Inflammatory Pain [14]. Given SDV attenuates pain originated from extraterritorial area which is not innervated by vagus nerve, supraspinal mechanisms are highly likely to contribute to SDV-induced analgesia in somatic pain conditions.…”
Section: Introductionsupporting
confidence: 78%
“…Moreover, SDV reduces pro-inflammatory gene expression in brain regions such as the basolateral amygdala (BLA) and central amygdala (CeA) in LPS-induced inflammatory pain condition [15]. We also observed that SDV produces pain reduction only in the second phase, not the first phase, of formalin test under acute inflammatory pain condition [14], which is consistent with a previous report [13]. As the second phase of formalin test is known to be mediated by central mechanisms [16,17], brain mechanisms might be also involved in SDV-induced analgesia.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is well known that the endocannabinoid system plays an important role in pain modulation. In fact, the activation of CB1R is able to suppress pain signaling at the supraspinal, spinal and peripheral levels [ 57 ]. The endocannabinoid system can also modulate fibrosis and inflammation: its activation, in fact, can suppress proinflammatory cytokines such as IL-1beta and TNF-alpha and increase anti-inflammatory cytokines, providing antifibrotic activity [ 58 ].…”
Section: The Nervous Fibers Of the Fasciamentioning
confidence: 99%
“…Cattle was provided with a diet adhering to the specifications outlined in the Polish Feeding Standard, formulated to fulfill the nutritional needs for total digestible nutrients and crude protein (Włodarczyk and Budvytis, 2011). Bulls were fasted for a period of 12 hours before slaughter, and according to available knowledge, short term fasting should not affect the tested receptors (Lee et al, 2020). The sample size was determined using general guidelines for morphological sciences (Henry et al, 2016).…”
Section: Animalsmentioning
confidence: 99%